2020
DOI: 10.1177/1077546320933477
|View full text |Cite
|
Sign up to set email alerts
|

Active vibration control development in ultra‐precision machining

Abstract: This study presents a combined feedback–feedforward adaptive regulator applied to an active vibration control tool holder platform to contain the effect of machining vibrations. The proposed mechatronic solution can be integrated in a milling machine tool as an interface between the beam ( Z-axis) and the tool holder. The aim is to counteract vibrations in the broadband frequency range (100 Hz–900 Hz), controlling the tool position in real time. The active vibration control system is based on the harmonic stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Chen et al [ 1 ] analyzed the change of assembly stress of the column joint surface of the heavy gantry machine tool; Guo and Yang [ 2 ] analyzed and studied the vibration modes, natural frequencies, and maximum deformation areas of the column bed of NC machine tool with ANSYS; Yu et al [ 3 ] studied improving the vibration resistance, stability and finishing performance of machine tool columns; Zheng [ 4 ] studied the column structure of NC milling machine; Lv et al [ 5 ] analyzed the stress of machine tool column of vertical machining center according to the joint surface theory. Kim [ 6 ] analyzed and optimized the internal rib plate structure of the column of the multi-axis and multi-function machine tool; Guerkov et al [ 7 ] studied and analyzed the whole machine tool; Venugopal et al [ 8 ] found through research that the alternative materials of machine tool structure have high damping characteristics and small Young's modulus; Paweko et al [ 9 ] studied and improved the accuracy of machine tool stiffness evaluation; In the same year, Aggogeri et al [ 10 ] proposed a feedback feed active vibration controller to curb the vibration generated during machining.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [ 1 ] analyzed the change of assembly stress of the column joint surface of the heavy gantry machine tool; Guo and Yang [ 2 ] analyzed and studied the vibration modes, natural frequencies, and maximum deformation areas of the column bed of NC machine tool with ANSYS; Yu et al [ 3 ] studied improving the vibration resistance, stability and finishing performance of machine tool columns; Zheng [ 4 ] studied the column structure of NC milling machine; Lv et al [ 5 ] analyzed the stress of machine tool column of vertical machining center according to the joint surface theory. Kim [ 6 ] analyzed and optimized the internal rib plate structure of the column of the multi-axis and multi-function machine tool; Guerkov et al [ 7 ] studied and analyzed the whole machine tool; Venugopal et al [ 8 ] found through research that the alternative materials of machine tool structure have high damping characteristics and small Young's modulus; Paweko et al [ 9 ] studied and improved the accuracy of machine tool stiffness evaluation; In the same year, Aggogeri et al [ 10 ] proposed a feedback feed active vibration controller to curb the vibration generated during machining.…”
Section: Introductionmentioning
confidence: 99%
“…An active vibration isolation system has been widely applied in metrological, photoetching and medical fields as well as semiconductor industry. In the study of the active vibration isolation system for an AIG, research institutions have developed a variety of vibration isolation systems and achieved good effective improvements to measurement accuracy and sensitivity [83][84][85]. Hensley et al of the Stanford University, USA designed an experimental system with vertical ground motion and atomic gravimeter isolation as given in [86].…”
Section: Active Vibration Isolationmentioning
confidence: 99%
“…Simulating and analyzing these vibrations call for multi-physics modeling techniques as well as real-time controlling. Aggogeri et al [31] presented a combined feedbackfeedforward adaptive regulator, which uses a dynamic frequency observer with an updating amplitude-frequency-phase algorithm to an active vibration control tool holder platform to stabilize the vibrations in a milling machine tool. Figure 12 illustrates the designed controller architecture as a multiple-input multiple-output system for counteracting the passive vibrations due to periodic forces in the UPM equipment.…”
Section: Digital Twins-based Vibration Controlmentioning
confidence: 99%